The Relationship Between Psychological Distress and Sleep Quality Among Middle-Aged and Older Adults: The Moderating Effect of Gender - LEE, Szu-Ying; HUANG, Sheng-Miauh; HUNG, Chia-Tai; FANG, Su-Chen (The Journal of Nursing Research, 2025)
Background: Symptoms of psychological distress such as depression and anxiety as well as gender are known to be associated with sleep quality in middle-aged and older adults. However, little is known about the effect on sleep quality of interactions among these factors. Purpose: This study was developed to investigate the moderating effect of gender on the relationship between psychological distress and sleep quality in middle-aged and older adults. Methods: A cross-sectional design, secondary data analysis of data on 5,590 individuals aged ≥ 45 years from the Taiwan Biobank database (2009-2018) was used. In this database, psychological distress was assessed using the Patient Health Questionnaire-4, and sleep quality was assessed using a self-report, one-question scale. Demographic data and health-related variables were evaluated as potential confounding factors. A hierarchical regression was conducted to examine the moderating effect of gender on the relationship between psychological distress and sleep quality after adjusting for potential confounders. Results: The participants with severe psychological distress were found to have a lower mean quality of sleep than those without (p ＜ .01), and males returned a better mean quality of sleep score than females (p ＜ .01). Moreover, a significant interaction effect between psychological distress and gender on sleep quality score was found (b = 0.123, SE = 0.022, p = .03). In terms of participants with severe psychological distress, males reported significantly poorer sleep quality than females. Conclusions: The findings provide evidence that gender moderates the relationship between sleep quality and psychological distress. Also, in terms of individuals with severe psychological distress, males reported worse sleep quality than women, indicating psychological distress impacts sleep quality in men more than women. Nurses should be aware of these findings when working with clinical professionals to tailor gender-specific education interventions to improve sleep quality and psychological health.